An in vivo evaluation of the change in the pulpal oxygen saturation after administration of preoperative anxiolytics and local anesthesia - Krishna P. Shetty; Sarvepalli V. Satish; Krishnarao Kilaru; Kalyana Chakravarthi Ponangi; Alexander M. Luke; Srisha Neshangi (Tabriz University of Medical Sciences, 2016)
Background. Given the influence of systemic blood pressure on pulpal blood flow, anxiolytics prescribed may alter the pulpal blood flow along with the local anesthetic solution containing a vasoconstrictor. This study evaluated the impact of preoperative anxiolytics and vasoconstrictors in local anesthetic agents on pulpal oxygen saturation. Methods. Thirty anxious young healthy individuals with a mean age of 24 years were randomly selected using the Corah's Dental Anxiety Scale (DAS). After checking the vital signs the initial pulpal oxygen saturation (initial SpO2) was measured using a pulse oximeter. Oral midzolam was administered at a dose of 7.5 mg. After 30 min, the vital signs were monitored and the pulpal oxygen saturation (anxiolytic SpO2) was measured. A total of 1.5 mL of 2% lidocaine with 1:200000 epinephrine was administered as buccal infiltration anesthesia and 10 min the final pulpal oxygen saturation (L.A SpO2) was measured. Results. The mean initial (SpO2) was 96.37% which significantly decreased to 90.76% (SpO2) after the administration of the anxiolytic agent. This drop was later accentuated to 85.17% (SpO2) after administration of local anesthetic solution. Statistical significance was set at P<0.0001. Conclusion. High concentrations of irritants may permeate dentin due to a considerable decrease in the pulpal blood flow from crown or cavity preparation. Therefore, maintaining optimal blood flow during restorative procedures may prevent pulpal injury.